Pengaruh variasi makanan terhadap pertumbuhan maggot - Ma'ruf, Muhammad Muizzul; Rokhim, Saiku (Filogeni: Jurnal Mahasiswa Biologi, 2026)
One solution currently being developed is the use of Hermetia illucens larvae as natural decomposers in organic waste treatment. This study aims to determine the effect of feed medium variation on the fresh weight and dry weight of larvae, as well as to evaluate the potential of larvae as agents for the bioconversion of organic waste. The method used was a Completely Randomized Design (CRD) with one factor, namely the type of feed substrate (tofu dregs, corn pulp, and vegetable waste). Each treatment was repeated 9 times, resulting in a total of 27 experimental units. The results showed that the type of feed medium had a significant effect on larval growth and productivity. Soybean curd residue (P3) produced the best growth due to its more balanced and easily digestible nutritional content. The results of the statistical method analysis (Anova) test showed a significance value of less than 0.05 (p < 0.05), indicating that there was a statistically significant difference between the treatment groups, which indicated that the type of feed medium given had a significant effect on the fresh weight and dry weight of the maggots. The highest substrate reduction efficiency (WRI) was found in media with low crude fiber content, while the lowest WRI occurred in corn bran, which contains lignocellulose that is difficult to degrade. The findings of this study indicate that H. illucens larvae have the potential to be developed as an efficient and environmentally friendly organic waste bioconversion technology, while also supporting sustainable waste management strategies.